2008
DOI: 10.1177/1359105307084311
|View full text |Cite
|
Sign up to set email alerts
|

Not Just `Skin Deep'

Abstract: This study examined links between anxiety pertaining to having one's skin evaluated by others and intention to participate in sport/exercise, general self-esteem and dermatological quality of life. Data assessing dermatological-related social anxiety, perceived acne severity, intention to participate in sport/exercise, self-esteem and dermatological quality of life were obtained from 50 acne patients. Results showed dermatological-related social anxiety to be negatively associated with intention to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 35 publications
1
24
0
2
Order By: Relevance
“…Loney et al [17] found that ‘participants who experience greater levels of skin-related social anxiety report lower intention to participate in sport and exercise’. Many of the subjects in this study who identified sports as an HRQoL factor were conscious about exposing their skin, whereas for others the physical symptoms of their disease prevented them from participating.…”
Section: Discussionmentioning
confidence: 99%
“…Loney et al [17] found that ‘participants who experience greater levels of skin-related social anxiety report lower intention to participate in sport and exercise’. Many of the subjects in this study who identified sports as an HRQoL factor were conscious about exposing their skin, whereas for others the physical symptoms of their disease prevented them from participating.…”
Section: Discussionmentioning
confidence: 99%
“… Potential Pathways of the Gut-Brain-Skin Axis in Acne Vulgaris : [1] Psychological distress alone or in combination with [2] high fat diet, processed comfort foods devoid of fiber, cause alterations to [3] gut motility and microbiota profile [4]. Loss of normal microbial biofilm ( Bifidobacterium in particular) causes intestinal permeability and endotoxins gain systemic access [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, acne is associated with anxiety, depression [5], feel of anger [6], and lower body satisfaction [7]. It can be negatively associated with intention to participate in sports and exercise [8]. …”
Section: Introductionmentioning
confidence: 99%